Exploring the Influences of Temperature on “H-Shaped” Glycerol Dialkyl Glycerol Tetraethers in a Stratigraphic Context: Evidence From Two Peat Cores Across the Late Quaternary - Tang, Xiaotong; Naafs, B. David A.; Pancost, Richard D.; Liu, Zhao; Fan, Tongyu; Zheng, Yanhong (Frontiers in Earth Science, 2021)
Unusual “H-Shaped” branched and isoprenoidal glycerol monoalkyl glycerol tetraethers (GMGTs, or H-GDGTs) have been found in peat, lake, and ocean sediments. A survey of recent samples from a modern global peat database suggested that there is a relationship between the abundance of H-GDGTs relative to regular GDGTs and temperature. However, this relationship has not been widely explored, including in a historical, stratigraphic or geological context. Here, we report the abundance and distribution of H-iso- and H-brGDGTs in two (Hani and Gushantun) peat cores from northeastern China through the late Quaternary (last 15 kyr) to examine whether the relationship between temperature and the relative abundance of H-GDGTs is preserved downcore. The results indicate that high relative abundances of H-brGDGTs are associated with high (or increasing) reconstructed mean annual air temperature (MAATpeat), albeit with considerable divergence in some intervals. On the other hand, high relative abundances of H-isoGDGTs are generally associated with low (or decreasing) MAATpeat. These findings are partly inconsistent with the observations from the modern database of globally distributed peats, which showed that the abundance of both (br- and iso-) H-GDGTs is positively correlated with temperature. The deviation in the relationship between H-isoGDGTs and temperature suggests that additional factors, for example pH and shifts in archaeal community related to hydrology, exert an influence on the abundance of H-isoGDGTs on the long-term.